Inter-Organizational Cost Management and Open Book Accounting: A Review - DhaifAllah, Bakil; Md Auzair, Sofiah; Maelah, Ruhanita; Ismail, Md Daud (Asian Journal of Accounting Perspectives, 2016)
This paper aims to review the recent literature on inter-organizational cost management (IOCM) and open book accounting (OBA) practices, and their relationship with cost reduction. Based on the method used, a comprehensive review of relevant literature on this topic between 1992 and 2016, was sourced, collected, and summarized. Subsequently, two major findings were drawn. First, studies in the US, UK, and Japan dominated research on the area of IOCM and OBA, but, in recent years, more European and other countries are becoming involved. Second, the reviewed studies show that IOCM and OBA improve inter-organizational relationships, particularly, when the partners develop relational safeguards to prevent opportunism. However, the conclusions from the conceptual and case studies on the role of IOCM and OBA to reduce costs in the supplier-buyer relationships were contradictory. This paper furthers the understanding of the contributions introduced in prior studies on IOCM and OBA, and helps to identify some future research directions. Keywords: Inter-Organizational Cost Management, Open Book Accounting JEL Classification: M41, M49